Exploring the relationship between nanoscale dynamics and macroscopic rheology in natural polymer gums. Issue 46 (2nd November 2016) - Grein-Iankovski, Aline; Riegel-Vidotti, Izabel C.; Simas-Tosin, Fernanda F.; Narayanan, Suresh; Leheny, Robert L.; Sandy, Alec R.
Abstract : Intensity correlation functions for gold nanoparticles in GN gum dispersions at various gum concentrations. Abstract : We report a study connecting the nanoscale and macroscale structure and dynamics of Acacia mearnsii gum as probed by small-angle X-ray scattering (SAXS), X-ray photon correlation spectroscopy (XPCS) and rheology. Acacia gum, in general, is a complex polysaccharide used extensively in industry. Over the analyzed concentration range (15 to 30 wt%) the A. mearnsii gum is found to have a gel-like linear rheology and to exhibit shear thinning flow behavior under steady shear. The gum solutions exhibited a steadily increasing elastic modulus with increasing time after they were prepared and also the emergence of shear thickening events within the shear thinning behavior, characteristic of associative polymers. XPCS measurements using gold nanoparticles as tracers were used to explore the microscopic dynamics within the biopolymer gels and revealed a two-step relaxation process with a partial decay at inaccessibly short times, suggesting caged motion of the nanoparticles, followed by a slow decay at later delay times. Non-diffusive motion evidenced by a compressed exponential line shape and an inverse relationship between relaxation time and wave vector characterizes the slow dynamics of A. mearnsii gum gels. Surprisingly, we have determined that the nanometer-scale mean square displacement of the nanoparticles showed a close relationship to the values predicted from the macroscopic elastic properties of the material, obtained through the rheology experiments. Our results demonstrate the potential applicability of the XPCS technique in the natural polymers field to connect their macroscale properties with their nanoscale structure and dynamics.